The Form of the Mortgage Contract - Miščević, Nikolina B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
This paper analyzes the form of the mortgage contract as one of the essential conditions for the conclusion of a valid contract. Considering that in 2015 Public Notary Law and Mortgage Law were amanded, the paper shows valid legal solutions related to the form of the mortgage contract. In addition, the author points out, firstly, the influence of the content of the mortgage contract on its form and, secondly, the influence of the form and the content of the contract on the process of settlement of a claim from the value of а mortgaged real estate.